Die Häufigkeit meteorologischer Fronten über Europa und ihre Bedeutung für die klimatische Gliederung des Kontinents. Ein Beitrag zur synoptischen Klimageographie - Eriksen, Wolfgang (ERDKUNDE, 1971)
Analysis of the frequency distribution of meteorological fronts in the European area cannot lead to a distinctive climatic division of the area. With, however, the help of this analysis, a satisfactory explanation can be given for general climatic phenomena which have not until now been adequately dealt with, such as the regional distribution of cloud and sunshine duration, or precipitation regime, which often shows pronounced variations over small areas. The frontal frequency, which is influenced by the major relief forms of the continent, especially barrier mountain ranges, is revealed as a clear climatic influence in its spatial-temporal changes. The analysis was able to contribute to a genetic justification of existing climatic classifications (especially the division based on seasonal climates of the earth, cf. Troll/Paffen 1964) and to provide suggestioned for a more detailed differentiation of the main climatic areas which, in almost all classifications, are often very large. The very different regional and seasonal frequencies of fronts (in total and according to type) could be the basis for such a sub-division.